REFORM OF MINING AND ENERGY LAW IN INDONESIA: THE CHALLENGES OF THE TRANSITION TO GREEN ENERGY AND ECOLOGICAL JUSTICE - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Economic and legal reforms in Indonesia’s mining and energy sectors, introduced through the Mining and Energy Law No. 2 of 2025, establish a progressive framework that supports mineral downstreaming, equal opportunities for state-owned enterprises and SMEs, and alignment with the 2025 National Energy Policy (KEN) to ensure energy security. However, the transition to green energy faces multiple challenges: resistance from the fossil fuel industry, a revision of renewable energy targets from 23% to 17–19%, deforestation caused by nickel mine expansion, and social inequality resulting from the closure of coal-fired power plants, which threatens workers in producing regions. Ecological justice—as a constitutional right to a healthy environment (1945 Constitution, Article 28H)—demands a Just Transition framework akin to the JETP, the integration of ESG principles, and regulatory harmonisation to balance economic, social, and environmental considerations. This systematic legal literature review concludes that holistic reform is necessary for Indonesia to achieve Net Zero Emissions by 2060 in a fair and sustainable manner, with recommendations for harmonising the Mining Law and the Job Creation Law, as well as strengthening the participation of indigenous communities.